Topical corticosteroid phobia in atopic dermatitis: International feasibility study of the TOPICOP score. Issue 11 (22nd May 2017) - Stalder, J.‐F.; Aubert, H.; Anthoine, E.; Futamura, M.; Marcoux, D.; Morren, M.‐A.; Trzeciak, M.; Szalai, Z.; Veres, K.; Deleuran, M.; Vestergaard, C.; Boralevi, F.; et al.
Abstract: Background: Adherence to topical corticosteroids (TCS) is essential for the effective treatment of atopic dermatitis but can be limited by concerns about their use. This study examined the feasibility of applying the validated TOPICOP score for assessing TCS phobia across different countries. Methods: This was a prospective multicentre feasibility study conducted in 21 hospitals in 17 countries. Patients >3 months of age with atopic dermatitis or their parents or legal representatives completed a validated translation of the TOPICOP questionnaire in the country's native language. Respondents also completed questionnaires collecting opinions about the feasibility and acceptability of the TOPICOP questionnaire. Results: A total of 1564 participants in 15 countries were included in the analysis. 81% of respondents considered the questions clear or very clear, and 79% reported that it took less than 5 minutes to complete. Each of the individual items in the TOPICOP questionnaire was considered to be not at all difficult to answer by 49% to 74% of participants. The mean global TOPICOP score was 44.7%±20.5. Mean TOPICOP subscores were 37.0±22.8% for knowledge and beliefs, 54.7±27.8% for fears and 50.1±29.1% for behaviours. Global scores and subscores differed between countries, although the subscores did not always vary in parallel, suggesting different levels of TCS phobia and different drivers for each country. Conclusions: The TOPICOP score can be feasibly applied across countries and may therefore be useful for obtaining qualitative and quantitative data from international studies and for adapting patient education and treatment.